Abstracts of free communications at EuroPD congress in Bruges, 2023-11-27 - Congrès EuroPD 2023 (RDPLF, 2023)
This special issue of the Home Dialysis Bulletin (crossref registered as Bulletin de la Dialyse à Domicile (BDD) )contains all abstracts submitted to the 2023 EuroPD congress. The abstracts are available in English and French at the same URL. Many of these abstracts reflect work of particular interest to clinicians and nurses and should be developed into a full article. We therefore encourage authors to write a full article and submit it to the BDD at https://www.bdd.rdplf.org. They will be double-blind peer-reviewed and, if accepted, will be published promptly in both languages to ensure the widest possible dissemination. The BDD endorses the Diamond Open Access Action Plan and follows its model (Diamond OA scholarly Communication Ecosystem); it is therefore free of charge for authors and readers and accessible to all health professionals and patients. Ethical considerations: before submitting their abstracts, all authors were informed that their articles would be published in the BDD and translated into French. Authors retain the copyright of their articles. Declaration of interests: Publication of these abstracts is provided free of charge by the French Registry of Peritoneal Dialysis and Home Hemodialysis. No payment or grant has been received from EuroPD or any third party for this work. Copyright: authors retain copyright.